N-acetylcysteine attenuates iodine contrast agent-induced nephropathy in 5/6-nephrectomized rats - Sochman, Jan; Peregrin, Jan H; Bürgelová, Marcela; Kopkan, Libor; Kramer, Herbert J; Cervenka, Ludek (Kidney & blood pressure research, 2010)
AIMS: In the present study we tested the efficacy of N-acetylcysteine (NAC) to minimize nephrotoxic effects of iodine contrast agents in intact rats as well as in 5/6-nephrectomized (5/6-Nx) rats. METHODS: Rats were allocated to a group of intact rats (n = 42) and a group of 5/6-Nx rats (n = 42). After 1 month of recovery from surgery, 5/6-Nx rats and intact (sham-operated) animals received either 6 ml/kg body weight (b.w.) meglumine ioxithalamate (Telebrix 350) or 6 ml/kg b.w. iohexol (Omnipaque 350) intravenously with or without pretreatment with 100 mg/kg b.w. NAC. Plasma and urinary concentrations of creatinine, sodium and protein in 24-hour urine collections were determined prior to and on days 1, 3 and 7 after drug administration. RESULTS: In intact animals, contrast agents caused no significant changes in kidney function throughout the duration of the experiment. In contrast, significant increases in plasma creatinine levels and decreases in creatinine clearance were induced by both contrast agents in 5/6-Nx rats. These changes were significantly attenuated by NAC pretreatment. CONCLUSION: The results of the present study demonstrate that iodine contrast agent-induced nephropathy in 5/6-Nx rats is significantly attenuated by intravenous pretreatment with NAC.
Keywords: nemoci ledvin; Animals; Iodine; Premedication; acetylcystein; Nephrectomy; Kidney Diseases; johexol; kontrastní látky; krysa rodu Rattus; Iothalamate Meglumine; jod; meglumin-jothalamát; zvířata; Iohexol; Contrast Media; Rats; premedikace; nefrektomie; Acetylcysteine